PERKEMBANGAN PARTISIPASI PEREMPUAN DALAM PARTAI POLITIK (STUDI KOMPARATIF INDONESIA DAN FILIPINA) - Irsalina, Nadira; Atthahara, Haura (Fakultas Politik Pemerintahan, 2022)
This study discusses the development of women's participation and justice in political rights in Indonesia and the Philippines. This issue is considered important to be discussed because it relates to gender equality which must be addressed immediately, because it involves human rights. In this study, the author uses a qualitative method, using library research data collection methods. namely by collecting data, documents, books, articles and scientific papers, which are in accordance with the object of research, which are then analyzed, reduced, and concluded. The results of this study found that there are similarities and differences with the development of women's participation in Indonesia and in the Philippines, both of which have a history of developing in a better direction. between the two Philippines countries, it is a country that upholds gender equality, even this is confirmed by the Global Gender Gap Global Economic Forum (WEF) report, based on this fact, it is hoped that it will encourage and motivate Indonesia in terms of gender, especially in the political fiel